2017
DOI: 10.1021/acsami.7b12120
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of Short Cationic Peptidopolysaccharide Self-Assembled by Hydrogen Bonding with Antibacterial Effect against Multidrug-Resistant Bacteria

Abstract: Cationic antimicrobial peptides (AMPs) and polymers are active against many multidrug-resistant (MDR) bacteria, but only a limited number of these compounds are in clinical use due to their unselective toxicity. The typical strategy for achieving selective antibacterial efficacy with low mammalian cell toxicity is through balancing the ratio of cationicity to hydrophobicity. Herein, we report a cationic nanoparticle self-assembled from chitosan-graft-oligolysine (CSM5-K5) chains with ultralow molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 71 publications
0
89
0
Order By: Relevance
“…Antimicrobial peptides (AMPs) are of interest as alternatives to traditional antibiotics because of their broad spectrum antimicrobial properties and efficacy against MDR bacteria; however, to date they have met limited success due to their often non-selective toxicity (3236). We previously reported that chitosan based cationic polymers showed antimicrobial activity against a variety of MDR pathogens (12, 2022). In this study, we demonstrate that CSM5-K5 is synergistically active with traditional antibiotics against three antimicrobial resistant pathogens growing as biofilms in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Antimicrobial peptides (AMPs) are of interest as alternatives to traditional antibiotics because of their broad spectrum antimicrobial properties and efficacy against MDR bacteria; however, to date they have met limited success due to their often non-selective toxicity (3236). We previously reported that chitosan based cationic polymers showed antimicrobial activity against a variety of MDR pathogens (12, 2022). In this study, we demonstrate that CSM5-K5 is synergistically active with traditional antibiotics against three antimicrobial resistant pathogens growing as biofilms in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…CSM5-K5 is a cationic nanoparticle that is self-assembled from chitosan-graft-oligolysine chains with ultralow molecular weight (1450 Da) that selectively kills bacteria with minimal toxicity toward mammalian cells (12). Hydrogen bonding within CSM5-K5 causes the polymer chains to aggregate into small nanoparticles to concentrate the cationic charge of the lysine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations